Effects of dietary nitrate, caffeine, and their combination on 20-km cycling time trial performance - Glaister, M.; Pattison, J. R.; Muniz-Pumares, D.; Patterson, S. D.; Foley, P. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to examine the acute supplementation effects of dietary nitrate, caffeine, and their combination on 20-km cycling time trial performance. Using a randomized, counterbalanced, double-blind Latin-square design, 14 competitive female cyclists (age: 31 ± 7 years; height: 1.69 ± 0.07 m; body mass: 61.6 ± 6.0 kg) completed four 20-km time trials on a racing bicycle fitted to a turbo trainer. Approximately 2.5 hours before each trial, subjects consumed a 70-ml dose of concentrated beetroot juice containing either 0.45 g of dietary nitrate or with the nitrate content removed (placebo). One hour before each trial, subjects consumed a capsule containing either 5 mg/kg of caffeine or maltodextrin (placebo). There was a significant effect of supplementation on power output (p = 0.001), with post hoc tests revealing higher power outputs in caffeine (205 ± 21 W) vs. nitrate (194 ± 22 W) and placebo (194 ± 25 W) trials only. Caffeine-induced improvements in power output corresponded with significantly higher measures of heart rate (caffeine: 166 ± 12 b/min vs. placebo: 159 ± 15 b/min; p = 0.02), blood lactate (caffeine: 6.54 ± 2.40 mmol/L vs. placebo: 4.50 ± 2.11 mmol/L; p < 0.001), and respiratory exchange ratio (caffeine: 0.95 ± 0.04 vs. placebo: 0.91 ± 0.05; p = 0.03). There were no effects (p >= 0.05) of supplementation on cycling cadence, rating of perceived exertion, VO2max, or integrated electromyographic activity. The results of this study support the well-established beneficial effects of caffeine supplementation on endurance performance. In contrast, acute supplementation with dietary nitrate seems to have no effect on endurance performance and adds nothing to the benefits afforded by caffeine supplementation.